Dual growth factor release from collagen based multilayer films on ti-surfaces enhances periimplant bone formation and angiogenic activity: an experimental in-vivo study - Kauffmann, Philipp; Wolfer, Susanne; Behrens, Christina; Schlosser, Pauline; Dullin, Christian; Schirmer, Uwe; Liefeith, Klaus; Schliephake, Henning (Clinical oral implants research, 2026)
Objectives The aim of the present study was to assess the effect of dual growth factor release from collagen-based polyelectrolyte multilayer films (PEMs) on titanium implants on periimplant bone formation and angiogenetic activity in minipig mandibles. Material and Methods Disc shaped Ti implants (5 × 7 × 1 mm) were coated with polyelectrolyte multilayer films and loaded with rhBMP-2, rhVEGF165, and a combination of both. Uncoated and unloaded Ti implants served as controls. The implants were inserted press-fit into 5 mm trephine cavities in minipig mandibles and evaluated after 4 and 13 weeks for bone formation, bone implant contact, and periimplant expression of CD31. Results After 4 weeks, there was no significant difference in periimplant bone formation nor bone-implant contact between the different surface conditions. CD31 expression was significantly increased around PEM coated implants loaded with VEGF and BMP each. After 13 weeks, bone implant contact and bone formation were significantly increased only around PEM coated implants with simultaneous release of BMP-2 and VEGF165. Expression of CD31 was significantly enhanced around all PEM coated implants loaded with growth factors regardless of the type or combination. Conclusion It is concluded that simultaneous release of rhBMP-2 and rhVEGF165 may be required to achieve significant improvement of periimplant bone formation and bone implant contact. Angiogenesis as reflected by CD31 expression is enhanced by both rhVEGF165 and rhBMP-2 to a similar extent without an additive effect of simultaneous release.